Establishing the Baby-Friendly Community Initiative in Italy: development, strategy, and implementation. - Bettinelli, Maria Enrica; Chapin, Elise M; Cattaneo, Adriano (J Hum Lact, 2012)
BACKGROUND: The Baby-Friendly Hospital Initiative (BFHI), developed by the World Health Organization and the United Nations Children's Fund (UNICEF) to promote breastfeeding in maternity facilities worldwide, has had a global impact on breastfeeding outcomes, but other interventions are needed both before and after hospital discharge to meet the recommended targets at 6 months. The Baby-Friendly Community Initiative (BFCI), a multifaceted program for community-based breastfeeding promotion that is complementary to the BFHI, addresses this challenge. OBJECTIVE: To describe the development, strategy, and implementation of the BFCI in Italy. METHODS: In 2006, UNICEF Italy created a working group to develop the BFCI for the Italian health system. A review of the different BFCI models worldwide was conducted. A preliminary adaptation of tools to Italian community health care settings was developed in 2007, when the Italian BFCI Seven Steps were published. Two years later, UNICEF Italy launched the Standards for Best Practice for both hospitals and communities, based on 2009 BFHI and UNICEF UK BFCI materials. OUTCOMES: The main outcome was to promote this process in Italian regional health systems and develop tools to assess compliance with the BFCI criteria. There is now one fully accredited Baby-Friendly Community in Italy, and 17 other communities are working on the various stages. CONCLUSIONS: The BFCI, a complex program that involves participation, training, audits, a continuous flow of feedback, and provision of resources for health workers and families, is now a reality in Italy.
Keywords: Breast Feeding; Continuity of Patient Care; Delivery Rooms; Female; Health Policy; Humans; Infant; Infant Care; Infant Welfare; Infant, Newborn; Italy; Maternal Health Services; Organizational Policy; Outcome and Process Assessment (Health Care); Practice Guidelines as Topic; Pregnancy; Program Development; Program Evaluation; United Nations; World Health Organization